Identity Papers Literacy and Power in Higher Education - Williams, Bronwyn T (University Press of Colorado, 2006)
How do definitions of literacy in the academy, and the pedagogies that reinforce such definitions, influence and shape our identities as teachers, scholars, and students? The contributors gathered here reflect on those moments when the dominant cultural and institutional definitions of our identities conflict with our other identities, shaped by class, race, gender, sexual orientation, location, or other cultural factors. These writers explore the struggle, identify the sources of conflict, and discuss how they respond personally to such tensions in their scholarship, teaching, and administration. They also illustrate how writing helps them and their students compose alternative identities that may allow the connection of professional identities with internal desires and senses of self. They emphasize how identity comes into play in education and literacy and how institutional and cultural power is reinforced in the pedagogies and values of the writing classroom and writing profession.